Pemberdayaan Masyarakat Melalui Demonstrasi Pembuatan Abon Lele dan Ayam Terfortifikasi Daun Kelor dan Bayam Merah sebagai Upaya Pencegahan Stunting - Endah Puji Astuti; Edhy Tri Cahyono; Pramitha Sari; Tri Sunarsih; Elvika Fit Ari Shanti (The Journal of Innovation in Community Empowerment, 2025)
Background: Stunting remains a serious chronic nutritional problem in Indonesia, impacting physical and cognitive development, and long-term productivity. One preventative measure is to increase public access to nutritious, affordable, and easily accepted local food for children. The innovation of shredded meat floss made from catfish and chicken fortified with moringa leaves and red spinach offers a food alternative high in protein, iron, vitamin A, and antioxidants. Method: This community service activity was carried out through a demonstration of making fortified shredded meat floss using a participatory-educational approach. The method included a short lecture on nutrition and stunting, hands-on practice in making shredded meat floss, interactive discussions, and pre-test, post-test, and organoleptic product evaluations. Participants were 30 members of the Women Farmers Group (KWT) in Demangrejo Village, Sentolo, Kulon Progo, who play a strategic role in family food management. Results: The activity showed a 32% increase in participants' knowledge regarding balanced nutrition and stunting prevention. 80% of participants were able to name local food ingredients rich in protein and iron and understood the stages of making fortified shredded meat floss. Participant participation reached over 80% throughout all stages of the demonstration. The resulting fortified shredded meat received positive organoleptic ratings, with 90% rating the taste as savory, 83.3% rating the aroma as fragrant, and 80% rating the texture as crispy. Some participants expressed interest in developing the product as a home business due to its ease of preparation, availability of raw materials, and its market value. Conclusion: This demonstration activity successfully increased the community's capacity to utilize nutritious local food to prevent stunting.